A Validated Rp – Hplc Method For Simultaneous Estimation Of Vitamin A And Vitamin E In Multivitamin Tablet Dosage Form - ANURADHA.S.N.; ARUNKUMAR.S (International Journal of Pharma and Bio Sciences, 2012)
A simple, selective, rapid, precise and accurate reverse phase high performance liquid chromatographic method has been developed for simultaneous estimation of vitamin A and Vitamin E in multivitamin tablet dosage form. The method was carried out on waters 2695 separation module & waters 2996 PDA detectors with Xterra C 18 column (150 X 4.6 mm ) using Acetonitrile : methanol and water pumped at a flow rate of 1ml/min In the ratio of 85 : 15 : 5 as mobile phase at 30oC. The detection carried out at 280 nm. The intra and inter day precision was found to be less than 2% showing high precision of the assay method. The % recovery of the method was greater than 98% and RSD did not exceed 2% indicating high degree of accuracy of the proposed HPLC method. The %RSD for the robustness testing was also less than 2%. The proposed HPLC method can be used for the estimation of Vitamin A and Vitamin E in combined multivitamin tablet dosage forms.